Biocontrol of Alternaria alternata YZU, a causal of stem end rot disease on pitaya, with soil phosphate solubilizing bacteria - Do, Quang Trung; Luu, The Anh; Dinh, Mai Van; Pham, Bich Ngoc; Nguyen, Thi Thu Hang (Hue University Journal of Science: Natural Science, 2022)
Stem end rot is the most destructive disease caused by Alternaria alternata YZU in pitaya-growing regions of Vietnam. This study was conducted to characterize antagonistic phosphate-solubilizing bacteria (PSB) from rhizosphere soil for their biocontrol activities against A. alternata YZU and evaluate the effect of temperature, pH, and water activity on that antagonism. Among seven PSB isolated from 45 rhizosphere soil samples, PSB31 (identified as Bacillus sp. strain IMAU61039, Accession number: MF803700.1) exhibited the highest antagonistic activity against A. alternata YZU with an average inhibition diameter of 0.65 ± 0.05 cm. The results also show that the strain PSB31 controlled the mycelial growth of A. alternata YZU by secreting antifungal metabolites. The most potent inhibitory activity was identified under in vitro conditions of 25 °C, pH 7, and aw 1. The isolated PSB31 could be a potential biological control agent against A. alternata YZU.